Beyond the Issue of Ordination - Kroll, Una M. (The ecumenical review, 1988)
The alienation of sacramental life as a power to be used over and against the community is the basis of all false clericalism; such clericalism is deeply rooted in sexist symbols of domination and passivity. Women cannot ask to be ordained without questioning fundamentally this concept of clericalism.